The pirates of Somalia : ending the threat, rebuilding a nation - The World bank (Washington The World bank, 2012)
This riveting narrative examines the world of the Somalian pirates: how they live, the forces that have created piracy in Somalia, how they spend the ransom money, and how they deal with their hostages.
Boyah -- A short history of piracy -- Pirate lore -- Of pirates, coast guards, and fishermen -- Garaad -- Flower of paradise -- The land of Punt -- Momman -- The policemen of the sea -- The law of the sea -- Into the pirates' lair -- Pirate insider -- The cadet and the chief -- The freakonomics of piracy -- The road's end.
Originally published: New York : Pantheon Books, c2011.
"Updated and revised"--Cover.
Includes bibliographical references (pages 279-294) and index.
Keywords: Pirates -- Somalia; Piracy -- Somalia